AKTIVITAS AIR, KURVA SORPSI ISOTHERMIS SERTA PERKIRAAN UMUR SIMPAN FLAKE UBI KAYU DENGAN VARIASI PENAMBAHAN KORO PEDANG - Triana Lindriati; Maryanto Maryanto (Faculty of Agricultural Technology, University of Jember, 2016)
The aim of our study determined water activity value, moisture sorption isotherm characteristic and predicted shelf life of cassava flake with variation of jack bean addition. The purpose of jack bean addition in to the flake to increase protein content. The result showed that water activity content of flake with 30% jack bean addition was 0,21±0,0034; 25% addition was 0,29±0,0027 and 20% addition was 0,21±0,0041. The moisture sorption isotherm characteristic of the flake was adsorption type (type II). Oswin equation can be used to predict the moisture content of flake related with relative humidity of environment that suitable with sorption isotherm curve. Flake with 25% jack bean addition packed in HDPE, stored in 85% relatie humidity room had highest selft life, that was 284 days. The lowest shelf life was flake with 25% and 20% addition packed in LDPE, stored in 95% relative humidity. The value of the shelf life was 21 days Keyword: packaging, moisture sorption isotherm, shelf life, water activity, cassava flake, jack bean